Undercropping coffee with forage legumes - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1990)
ILCA (International Livestock Centre for Africa) trials in Ethiopia have shown that planting legumes under coffee trees can produce substantial amounts of high-quality forage and also increase yields of coffee. Coffee is the major cash crop of...